EQUIVALENCE OF PHRASEOLOGICAL UNITS BETWEEN ENGLISH AND UZBEK (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Somatism component phraseological units in English and Uzbek are common linguistic phenomena, component phraseological analysis, study of their structural structure and related semantics, and on this basis their comparison with component phraseological units in English and Uzbek languages. to compare is to generalize the features common to both languages and at the same time to reveal the phenomena specific to each of the languages being compared.